Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd002295.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Exercise interventions for smoking cessation

Abstract: Background Taking regular exercise may help people give up smoking by moderating nicotine withdrawal and cravings, and by helping to manage weight gain. Objectives To determine whether exercise-based interventions alone, or combined with a smoking cessation programme, are more effective than a smoking cessation intervention alone. Search methods We searched the Cochrane Tobacco Addiction Group Specialized Register in April 2014, and searched MEDLINE, EMBASE, PsycINFO, and CINAHL Plus in May 2014. Selection cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 169 publications
0
40
0
4
Order By: Relevance
“…Unfortunately, other clinical trials have yielded no significant benefit as adjunct cessation therapies, perhaps because they were underpowered Ussher et al, 2012Ussher et al, , 2014. The apparent beneficial effect on smoking cessation observed in at least some clinical trials may be due to a diminution in cue-induced craving , thus reducing the relapse rate.…”
Section: Clinical Evidencementioning
confidence: 99%
“…Unfortunately, other clinical trials have yielded no significant benefit as adjunct cessation therapies, perhaps because they were underpowered Ussher et al, 2012Ussher et al, , 2014. The apparent beneficial effect on smoking cessation observed in at least some clinical trials may be due to a diminution in cue-induced craving , thus reducing the relapse rate.…”
Section: Clinical Evidencementioning
confidence: 99%
“…Another growing body of research has evaluated the physical and psychological benefits of exercise and physical activity and has begun exploring potential treatment applications for exercise as a behavioral intervention (USDHHS 1996, Ussher et al 2012, Smith and Lynch 2011). Controlled laboratory studies in humans demonstrated that moderate-intensity aerobic exercise decreased cravings for alcohol (Ussher et al 2004), cigarettes (Daniel et al 2004), and cannabis (Buchowski et al 2011), while brief episodes of isometric (Ussher et al 2006, Ussher et al 2009) and aerobic (Ussher et al 2001, Daniel et al 2004, Williams et al 2011) exercise also alleviated symptoms of tobacco withdrawal.…”
Section: Introductionmentioning
confidence: 99%
“…CO or spirometry measurement) [100,101,102], incentive-based interventions [85,103,104], and hypnosis (even if men were more likely to respond than women) [105,106,107]. Positive associations are observed for acupuncture [107,108], increased physical activity [23,30,109,110] and aversive therapy [107,111], but the results are not significant. Improvement of SC is also related with the type of provider; e.g.…”
Section: Resultsmentioning
confidence: 99%